Differential gene signature in adipose tissue depots of growth hormone transgenic mice. (12th October 2020) - Duran‐Ortiz, Silvana; Young, Jonathan A.; Jara, Adam; Jensen, Elizabeth A.; Basu, Reetobrata; List, Edward O.; Qian, Yanrong; Kopchick, John J.; Berryman, Darlene E.
Abstract: Bovine growth hormone (bGH) transgenic mice mimic the clinical condition of acromegaly, having high circulating growth hormone (GH) levels. These mice are giant, have decreased adipose tissue (AT) mass, impaired glucose metabolism and a shortened lifespan. The detrimental effects of excess GH have been suggested, in part, to be a result of its depot‐specific actions on AT. To investigate this relationship, we evaluated gene expression, biological mechanisms, cellular pathways and predicted microRNA (miRNA) in two AT depots (subcutaneous [Subq] and epididymal [Epi]) from bGH and littermate controls using RNA sequencing analysis. Two analyses on the differentially expressed genes (DEG) were performed: (i) comparison of the same AT depot between bGH and wild‐type (WT) mice (genotype comparison) and (ii) comparison of Subq and Epi AT depots within the same genotype (depot comparison). For the genotype comparison, we found a higher number of significant DEG in the Subq AT depot of bGH mice compared to WT controls, corroborating previous reports that GH has a greater impact on the Subq depot. Furthermore, most of the DEG in bGH mice were not shared by WT mice, suggesting that excess GH induces the expression of genes not commonly present in AT. Through gene ontology and pathway analysis, the genotype comparison revealed that the DEG of the Subq depot of bGH mice relate to fatty acid oxidation, branched‐chain amino acid degradation and the immune system. Additionally, the AT depot comparison showed that the immune cell activation and T‐cell response appear up‐regulated in the Subq compared to the Epi AT depot. The miRNA prediction also suggested a modulation of T‐cell‐related biological process in Subq. In summary, the present study provides a unique resource for understanding the specific differences in gene expression that are driven by both excess GH action and AT depot location. Abstract : High circulating Growth hormone (GH) levels as seen in the giant bGH mice, leads to impaired glucose metabolism, and decrease adipose tissue (AT) mass and lifespan. RNA‐sequencing performed on the subcutaneous (Subq) and visceral AT of these mice, showed that differential gene expression, particularly of genes associated with immune response, may contribute to the metabolic dysfunction of mice with GH excess.